Understanding the European Union's Perception of the Threat of Cyberterrorism: A Discursive Analysis. (28th December 2021) - Baker‐Beall, Christopher; Mott, Gareth
Abstract: This article analyses the European Union's (EU) construction of the threat of cyberterrorism. Through the application of interpretive discourse analysis, the article identifies several key strands that underpin the construction of the cyberterrorist threat within the political and security institutions of the EU. Locating the analysis within the literature pertaining both to the EU as a security actor and to cyber‐security, the article identifies the emergence of the perceived threat of cyberterrorism within the EU discourse on emerging security threats. The article scrutinizes the meaning(s) ascribed to this threat, arguing that although cyberterrorism has not been conclusively defined by the EU, the threat has been invoked as a means of legitimizing existing and future security practices. In particular, the threat of cyberterrorism has been ascribed significance with respect to the need to implement harmonized, high standards for the securing of critical infrastructure across the EU and its member states.